E-book Based on Project Based Learning Assisted by Kvisoft Flipbook Maker Blended Learning in Elementary Schools - Desyandri; Feby Kharisna; Risda Amini; Yeni Erita (Jurnal Ilmiah Sekolah Dasar, 2024)
Blended learning is one innovation that can improve access to learning for large groups of students and their beliefs about how effective the learning environment is. Blended Learning combined with the book will make learning more interesting for students. This research aims to produce valid, practical, and effective using the R&D method and ADDIE models. The validation test was carried out in three stages, the first validation test by expert lecturers and practitioners obtained an average score of 92.75 in the very valid category. Second, in the validation stage, FGD participants obtained an average score of 90 with a very valid category. Third, the small group test validation stage obtained an average value of 89 with a very valid category. The practicality test was carried out in two stages. First, the practicality test of the teacher response questionnaire obtained an average score of 91 in the very practical category. Second, the practicality test of the student response questionnaire obtained an average score of 81 in the very practical category. The effectiveness test was carried out in two stages. First, testing the effectiveness of student activities obtained an average score of 84 in the very active category. The two effectiveness tests of student learning outcomes obtained an average score of 90 in the very effective category. From the researchers' findings, it can be concluded that e-book-based Project Based Learning help Kvisoft Flipbook Maker Blended Learning in elementary schools is very valid, practical, and effective for use in learning in elementary schools.